Fundamentals of silico-ferrite of calcium and aluminium (SFCA) and SFCA-I iron ore sinter bonding phase formation: effects of mill scale addition. (22nd August 2017) - Webster, Nathan A. S.; Pownceby, Mark I.; Pattel, Rachel
Abstract : The thermal decomposition of mill scale, and the effect of mill scale addition on the formation and decomposition of Silico-Ferrite of Calcium and Aluminium (SFCA) and SFCA-I iron ore sinter bonding phases, has been investigated using in situ X-ray diffraction. Application of the external standard method of quantitative phase analysis of the in situ data collected during decomposition of the mill scale highlighted the applicability of this method for the determination of the nature and abundance of amorphous material in a mineral sample. Increasing mill scale addition from 2.6 to 10.6 and to 21.2 wt% in an otherwise synthetic sinter mixture composition designed to form SFCA did not significantly affect the thermal stability ranges of SFCA-I or SFCA, nor did it significantly affect the amount of each of SFCA or SFCA-I, which formed. This was attributed to the low impurity (i.e. Mn, Mg) concentration in the mill scale, and also the transformation to hematite during heating of the wüstite and magnetite present in the mill scale, with the hematite available for reaction to form SFCA and SFCA-I.